La aplicación de la teoría de descubrimiento de Jerome Bruner y su relación con el aprendizaje de la trigonometría plana, en los estudiantes del tercer semestre de la escuela de ciencias, carrera de Ciencias Exactas, durante el período septiembre 2013 – octubre 2014 - Cabay Valla, Mónica Alexandra (2016)
The present research has as its theme "THE APPLICATION OF JEROME BRUNER S DISCOVER THEORY AND ITS RELATIONSHIP WITH LEARNING TRIGONOMETRY FLAT IN THIRD SEMESTER STUDENTS OF SCHOOL OF SCIENCE, SCIENCE CAREER DURING THE PERIOD SEPTEMBER 2013 - OCTOBER 2014 ", allowing it to analyze the contents of the subject of Trigonometry Syllabns for the Third Semester of the School of Sciences, the existing problem is that much of the teachers of Mathematics has poor training, as for the mathematical and methodological knowledge. This research was conducted with 11 students of the third semester, the analytic-synthetic hypothetical-deductive and inductive-deductive method was used, the kind of research is descriptive and explanatory, the design is lengthwise cutting, as techniques the field research and literature were used, for gathering information a survey was applied and evaluation activities of the tutorial was handled too. As a solution to the problem described above a tutorial based on the Theory of Jerome Bruner discovery was made. The results of evaluation of the use of the guide in students are: 82% of students performing exercises easily that allows to conclude that the use of teaching resources in a class help in the learning process, even more so when students are those who are building then own knowledge in an active way, these arguments serve to recommend to all teachers the implementation of new strategies and methodologies where the student will be allowed the option to discover and create their own knowledge.